ХөГЖИЖ БУй ОРнУУд даХЬ БЮРОкРаТ УдИРдЛаГЫн өнөөГИйн ТөЛөв, цааШдЫн ХандЛаГа - Ц.БАТБОЛД (Politology, 2023)
Товч агуулга: Олон шинжээчид өнөөгийн эрх баригчдын удирдах үйл ажиллагааг хангалтгүй төвшинд байна гэж үздэг. Мэргэжилтнүүд дэлхийн нийт хүн амын 51 хувьтай тэнцэх хэмжээний, шилжилтийн нийгэм бүхий хөгжиж буй 16 оронд судалгаа хийжээ. Дэлхий дээрх Засаглалын Судалгааны (WSG) төвөөс гаргасан энэхүү судалгааны гол зорилго нь шинэ тогтолцоог нэвтрүүлэх явдал юм. Бюрократ ёс нь зөвхөн хувь хүний хэмжээнд бус засаглалын хүрээнд судлагдах учиртай. Хүнд суртлыг бий болгож буй албан болон албан бус дүрэм журмууд нь төр хэрхэн үйл ажиллагаа явуулж буйд чухал нөлөөтэй. Засгийн газар болон иргэдийн хооронд байгуулсан олон гэрээ, санал хүсэлт, тусламж хүссэн хүсэлтийн хэрэгжилтийн үйл явц нь хүлээлт зэргээс үүдэн хүнд суртлыг бий болгосоор байгааг судалсан. Abstract: The framework for implementing policy is very important. Day-to-day management of government operations affects the impression citizens have not only of individual departments but often the regime(deglem) as a whole. In other words, how policy implementation is structured constitutes an important aspect of governance. The specific questions we used inthe WGS were:a)To what extent are higher civil servants a part of the policy-making process? (theinfluence. indicator); b) To what extent is there a merit-based system for recruitment into the civilservice? (the .meritocracy. indicator.); c) To what extent are civil servants accountable for their actions? (theaccountability. indicator); d) To what extent are there clear decision-making processes in the civil service? (thetransparency. indicator); e)To what extent is there equal access to public services? ( the .access. indicator); As reported in Working Paper 3, there is clearly much discontent (durguitsel)about the bureaucracy in many countries. The aggregate scores (niit onoo)are among the lowest of all the different arenas. The bureaucracy also records relatively modest improvement over time. There are plenty of references in the commentaries(tailbar) that nepotism(tanil talaa dewshuuleh) and various forms of corruption continue to affect the civil services in many countries. This section looks at two issues: (i) the aggregate scores for the countries, and (ii) the changes over time and some of the reasons behind these changes